Analysis via CFD of the battery interconnection pipeline circuit to the electric bus thermal management system - Okamoto, André Yudi Lima [UNESP]; Ribeiro, Danilo Albuquerque [UNESP]; Salviano, Leandro Oliveira [UNESP]; Pantaleão, Aluisio Viais [UNESP] (COBEM, 2023)
The use of numerical methods for predicting phenomena associated with a flow plays an important role in the development of new technologies and improvement of previously existing technologies in the area of Fluid Mechanics. In this way, the study of calculation methodology based on modern CFD (Computational Fluid Dynamics) corresponds to a great step towards the understanding of phenomena physics related to the flow, and can be used in a series of applications, such as ship hydrodynamics, aircraft aerodynamics, biomedical engineering, among others. The purpose of this work is to design an optimized duct circuit that interconnects the batteries to the thermal management system of an electric public urban transport vehicle (BEV – Battery Electric Vehicle), using free codes (open source software), and contribute to increasing the vehicle’s autonomy. One of the most important features of this cooling system is suitability for the operating climate, as that a change of 0.4 ◦C in the system can cause considerable loss of autonomy. For this study, different types of proposed insulator were simulated individually subject to a constant temperature in the external surface, with the possibility of multilayer if necessary. Using the OpenFOAM software, steady-state numerical simulations involving heat transfer were performed for the different types of insulation in order to obtain the maximum thermal efficiency. Numerical results obtained using the RAS k-ω SST turbulent model were expected to be close to the flow topology reported by experimental literature. It is proposed, then, to validate the numerical techniques developed here from databases of data from vehicle tests, specifically applied to the pipelines of the thermal management of the battery pack. The results allowed to determine the optimal cooling system among series of insulation, that provides the best thermal efficiency, contributing to autonomy of the vehicle. In addition, the robust and customized metodology employed allows extrapolation to other thermal vehicle systems.

A utilização de métodos numéricos para previsão de fenômenos associados a um escoamento desempenha um papel importante no desenvolvimento de novas tecnologias e no aprimoramento de tecnologias já existentes na área de Mecânica dos Fluidos. Desta forma, o estudo da metodologia de cálculo baseada em CFD (Computational Fluid Dynamics) corresponde a um grande passo na compreensão dos fenômenos físicos relacionados ao escoamento, podendo ser utilizada em uma série de aplicações, como hidrodinâmica de navios, aerodinâmica de aeronaves, engenharia biomédica, entre outros. O objetivo deste trabalho é projetar um circuito de dutos otimizado que interliga as baterias ao sistema de gerenciamento térmico de um veículo elétrico de transporte público urbano (BEV – Battery Electric Vehicle), utilizando códigos livres (software de código aberto), e contribuir para aumentar a autonomia do veículo. Uma das características mais importantes deste sistema de refrigeração é a adequação ao clima operacional, pois uma variação de 0,4 ◦C no sistema pode causar perda considerável de autonomia. Para este estudo foram simulados individualmente diferentes tipos de isoladores propostos sujeitos a uma temperatura constante na superfície externa, com possibilidade de multicamadas se necessário. Utilizando o software OpenFOAM, foram realizadas simulações numéricas em regime permanente envolvendo transferência de calor para os diferentes tipos de isolamento, a fim de obter a máxima eficiência térmica. Espera-se que os resultados numéricos obtidos usando o modelo turbulento RAS k-ω SST estejam próximos da topologia do escoamento relatada pela literatura experimental. Propõe-se, então, validar as técnicas numéricas aqui desenvolvidas a partir de bancos de dados de testes veiculares, aplicados especificamente às tubulações do gerenciamento térmico do conjunto de baterias. Os resultados permitiram determinar o sistema de refrigeração ideal entre séries de isolamentos, que proporcione a melhor eficiência térmica, contribuindo para a autonomia do veículo. Além disso, a metodologia robusta e flexível empregada permite a extrapolação para outros sistemas térmicos de veículos.
Análise via CFD de circuito de dutos de interligação das baterias ao sistema de gerenciamento térmico de ônibus elétrico
Keywords: CFD; OpenFOAM; Interconnection ducts; Thermal management; Suitability to the operating climate